Cyclin-dependent kinase 9 (CDK9) predicts recurrence in Middle Eastern epithelial ovarian cancer - Sandeep Kumar Parvathareddy; Abdul K. Siraj; Tariq Masoodi; Padmanaban Annaiyappanaidu; Ismail A. Al-Badawi; Fouad Al-Dayel; Khawla S. Al-Kuraya (Journal of Ovarian Research, 2021)
Abstract Background Cyclin-dependent kinase 9 (CDK9) has been shown to play an important role in tumorigenesis of several malignancies. However, the expression of CDK9 in ovarian cancer from Middle Eastern ethnicity remains unknown. Methods A tissue microarray of 441 epithelial ovarian cancer (EOC) samples was used to study the expression of CDK9 immunohistochemically and their clinico-pathological associations were determined. Cox proportional hazards regression model was used for univariate and multivariate analysis of recurrence-free survival. Results CDK9 over-expression was noted in 56.2 % (248/441) of EOCs and was associated with adverse clinico-pathological parameters such as distant metastasis (p < 0.0001), stage IV tumors (p < 0.0001), tumor recurrence (p = 0.0105) and high Ki-67 index (p < 0.0001). Importantly, CDK9 over-expression was an independent predictor of poor recurrence-free survival (Hazard ratio = 1.51; 95 % confidence interval = 1.15–1.98; p = 0.0030). We also found that CDK9 outperforms Ki-67 as a predictor of tumor recurrence in EOC. Conclusions Our results show that CDK9 expression correlates with markers of advanced disease in Middle Eastern EOC and is also a prognostic marker. CDK9 overexpression also identifies a subset of patients with highest likelihood of recurrence across the patient cohort. These patients may benefit from additional alternative therapies targeting CKD9.